Enabling Full Interaction with the Android System and Applications through Speech Recognition - Cunha, Emerson Barbosa da; Silva, Daniella Dias Cavalcante da; Vasconcelos, César Rocha (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Mobile devices , such as smartphones and tablets, have become almost indispensable items in people's daily lives. The interaction via touches on screen has been consolidated in these devices, being quite efficient, for the majority of the cases. However, this type of interaction can be limiting, or even make impossible the use of the device, for a person with busy hands or some kind of motor difficulty. In such cases, the possibility of using voice commands to control the device may be a more attractive solution. Although some devices already offer this kind of feature, it is restricted to some features pre-determined by the system. The main goal of this work was to develop an application that allows full interaction with the device via voice commands using the speech recognition API of the Android operating system. Recognition tests were performed with the developed application, whose results demonstrated a 95% efficiency, making possible a full interaction with any application installed in the device.